Direct evidence for toxin production by Pseudo-nitzschia plurisecta (Bacillariophyceae) and extension of its distribution area. Issue 4 (2nd October 2019) - Caruana, Amandine M.N.; Ayache, Nour; Raimbault, Virginie; Rétho, Michaël; Hervé, Fabienne; Bilien, Gwenael; Amzil, Zouher; Chomérat, Nicolas
ABSTRACT: We confirm an amnesic shellfish poisoning risk associated with domoic acid production by the species Pseudo-nitzschia plurisecta and determine the toxin profile, which includes three domoic acid isomers. Although the species was reported once in European waters, along the Spanish Atlantic coast, here we describe and characterize P. plurisecta collected during the first occurrence in French Atlantic waters. Three strains (IFR-PPL-15.1, 15.2 and 15.3) were isolated from French coastal water samples in June 2015. These strains were identified and characterized by microscopic observation, molecular (ITS region sequencing and phylogenetic analysis) and metabolite (toxins and pigments) analyses. The cell shape is lanceolate and the valve contains a central interspace with uniseriate stria of oval-square poroids, each divided into 3–10 sectors. The ITS gene sequence is homologous to the original sequence available for the Spanish strain P. plurisecta . The pigment profile contains chl a, c3, c2, fucoxanthin, diatoxanthin, diadinoxanthin and traces of β, β-carotene. Results on morphology, phylogeny and pigments led to the identification of P. plurisecta and confirmed its first occurrence in French waters.